Review on Indian Medicinal Plants/Herbs as Sources of Antioxidants - Satish Kanhar; Ashirbad Nanda; Biswajit Samantaray; Satyaprakash Dehury; Priyanka Priyadarsini; Jyotirmaya Nayak (Current Overview on Pharmaceutical Science Vol. 3, 2023)
Antioxidant molecules are pharmacologically active and have few or no adverse effects. These are currently being sought for application in preventative medicine and food industry around the world. The plants produce a lot of antioxidants to protect themselves from the oxidative stress induced by photons and oxygen, therefore they could be a good source of novel antioxidant molecules. Traditional herbal remedies play an essential role in India’s healthcare system. Ayurveda, the world’s oldest medicinal system, may hold the key to discovering active and therapeutically helpful chemicals in plants. In light of the increased interest in determining the antioxidant potential of herbal medicine, we addressed 20 no. of plants that have been found to have antioxidant properties in this review. Some of the plants examined are used in combination with other herbs, while others are used alone. Certain herbs such as Aerva lanata, Amaranthus paniculatus, Coriandrum sativum and Coccinia indica are utilized as vegetables, implying that these plants may provide dietary antioxidants.